Cardiovascular disease: risk assessment, total risk, and primary prevention in the general population. Insights from the Tromsø Study - Hagen, Amalie Nilsen (UiT The Arctic University of Norway, 2023)
Cardiovascular disease (CVD) is a major cause of mortality and morbidity, calling for an active preventive approach. Elevated blood pressure and cholesterol, smoking, diabetes, unhealthy diet, inactivity, and obesity are key risk factors for CVD development. Several risk factors combined may put an individual at a high total CVD risk. To measure total CVD risk, we used the NORRISK 2 score that estimates the 10-year risk of fatal and non-fatal myocardial infarction and stroke. This thesis used data from the population-based Tromsø Study, Tromsø6 (2007-2008), and Tromsø7 (2015-2016) to study total CVD risk and primary prevention in the general population. We observed a decline in total CVD risk during the time period and a change in the distribution from higher to lower risk categories. The NORRISK 2 score and the current primary prevention guidelines increase the population proportion at risk by 3.4 percentage points compared to the former risk score and guideline. Individuals with a high risk of CVD experienced several favourable changes in CVD risk factors between Tromsø6 and Tromsø7. However, less than 1 in 10 achieved all blood pressure, lipids, and smoking treatment targets combined. Individuals with the highest risk of CVD have the lowest probability of achieving treatment targets. Our results showed that medication use was the most important factor associated with target achievement. We have demonstrated a potential for improvement in the primary prevention of CVD, and more attention and closer follow-up of high-risk individuals are needed.